PERLINDUGAN HUKUM TERHADAP KORBAN KEJAHATAN TINDAK PIDANA NARKOTIKA BERKAITAN DENGAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Nugraha, Sandi; Windyastuti, Feny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2022)
Narcotics and psychotropics are drugs or materials that are useful in the fields of treatment, service, health, and scientific development, and on the other hand can cause very detrimental dependence if used without supervision, strict and careful supervision. Article 27 paragraph (1) of the 1945 Constitution affirms